The Effects of Glucose Fluctuation on the Severity of Coronary Artery Disease in Type 2 Diabetes Mellitus - Xingguang Zhang; Xiuping Xu; Xiumin Jiao; Jinxiao Wu; Shujing Zhou; Xiaofeng Lv (Journal of Diabetes Research)
Objectives. To explore the difference of glucose fluctuations between the normal subjects and diabetes mellitus (DM) patients and explore their impact on the development of CAD in type 2 DM patients. Methods. The subjects were divided into 3 groups: normal control (group A, ), type 2 DM patients without cardiovascular complications (group B, ), and type 2 DM patients with cardiovascular complications (group C, ). The SYNTAX scores were collected in group C. CGMS for 72 h was applied on all the subjects. The indexes such as MBG and the LAGE were calculated. Glycemic excursions were compared between groups A, B, and C, respectively. Results. The tested indexes had significant differences among the three groups. SYNTAX scores are related to systolic blood pressure, CRP, MAGE, and HbA1c and are significantly correlated at 6:00–8:00 and 11:00–13:00 time points in group C. Conclusions. Compared with normal subjects, T2DM patients have greater blood glucose fluctuations; T2DM patients with CAD have larger glucose fluctuations than T2DM patients without CAD. Blood glucose fluctuations are positively correlated with carotid artery intima-media thickness in T2DM patients and have a significant influence on the development of coronary artery.